Characteristics of Streptococcus pneumoniae Serotype 19A Isolates from Children in the Pre- and Post-Conjugate Vaccine Era. (4th October 2017) - Koutouzis, Emmanouil I; Daikos, George L; Chatzichristou, Panagiota; Michos, Athanasios; Tsakris, Athanasios; Koutouzi, Foteini I; Syriopoulou, Vassiliki
Abstract: Background: The aim of the present study was to assess the prevalence and characteristics of S. pneumoniae serotype 19A isolates from invasive and non-invasive pneumococcal disease (IPD) in children, before and after the introduction of pneumococcal conjugate vaccines (PCVs) in Greece. Methods: All S. pneumoniae isolates collected between 1986 and 2015 were re-cultured for further testing. Serotyping was performed using the quellung reaction and antibiotic susceptibilities were determined by E-test. The altered pbp genes ( pbp2b, pbp2x, and pbp1a ) conferring resistance to penicillin and the macrolide-resistant genes [mef(A), mef(E), and erm(B)] were detected by polymerase chain reaction (PCR) using specific primers. The sequence types (ST) and clonal complexes were determined by multilocus sequence typing (MLST). Results: Among 1, 875 isolates examined, 210(11.2%) (belonged to serotype 19A. The proportion of serotype 19A isolates increased from 4.6% (47/1018) in the pre-PCV7 years (1986–2005) to 19.6% (88/449) in the post-PCV7 years (2006–2010) and to 18.4% (75/408) in the post PCV-10 and PCV13 years (2011–2015).The resistance frequencies to penicillin, cefotaxime, erythromycin, clindamycin, and tetracycline increased significantly after 2005 as compared with the preceding period (1986–2005) from 8.5% to 31.9%, 2.1% to 20.8%, 10.6% to 65.6%, 4.2% to 47.7% and 19.1% to 46.0%, respectively ( P < 0.01). Moreover, 94 (57.7%) of 163 isolates after 2005 exhibited multidrug-resistant (MDR) phenotype, whereas only seven (15.9%) of 47 isolates from period 1986–2005 were MDR ( P <0.001). All the penicillin non-susceptible isolates examined ( N = 136), had altered one or more of the pbp genes. Of 112 erythromycin-resistant isolates, 22 contained the mefE gene, 39 the ermB and 51 both the mefE and ermB genes. MLST analysis of 31 invasive isolates revealed four clonal complexes (CC); CC172 ( n = 11), CC199 ( n = 8), CC320 ( n = 5), and CC276 ( n = 3), and four isolates belonged to CC2669, CC177, CC81, and CC63. The CC172 and CC199 were present throughout the study period, whereas the CC320 and CC276 appeared after 2009. Conclusion: S. pneumoniae serotype 19A increased significantly after the introduction of PCV7 and a substantial proportion of these isolates exhibited MDR phenotype. The majority of the examined isolates belonged to limited number of CC. Disclosures: V. Syriopoulou, Hellenic Center for Disease Control and Prevention: Grant Investigator, Research grant. Pfizer Inc.Pharmaceutical Company: Grant Investigator, Research grant